Evaluation of Government Bureaucracy in Public Administration Services at Rsud Dr. M. Yunus Bengkulu City - Bakat Seno Pratomo (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The research objective to be achieved in this research is to find out how to evaluate government bureaucracy in public administration services at RSUD Dr. M. Yunus, Bengkulu City. The type of research used in this research is qualitative research with a descriptive approach. Qualitative research with a descriptive approach is intended to provide an overview of the Evaluation of Government Bureaucracy in Public Administration Services at Dr. Regional Hospital. M. Yunus, Bengkulu City.The results of the research show that reliability in inpatient health services is good, the alertness of doctors and the skills of the staff at the Dr. Regional General Hospital. M Yunus Bengkulu City in handling inpatients, handling patients in accordance with applicable procedures, and always prioritizing professionalism in providing services to patients. Empathy (empathy), the ability to respond to patient complaints was responded well by the Regional General Hospital staff, Dr. M Yunus Bengkulu City. And the empathetic attitude of hospital employees is quite good in providing excellent service in accordance with the vision and mission of Dr. General Hospital. M Yunus Bengkulu City p. The responsiveness of health workers to patients is good, listening to patients' needs and complaints, but in terms of service, health workers do not apply speed in working according to patient expectations. A form of assurance by hospitals is to provide clear information regarding service times for each patient so that patients can visit at the specified time. Physical evidence (tangible), facilities and infrastructure at the Regional General Hospital dr. M Yunus Bengkulu City has been adequate and supportive in assisting inpatient services at hospitals. However, the inpatient facilities are not yet complete and maintenance still needs to be improved.